PENGEMBANGAN TUNGKU PELEBURAN ALUMINIUM UNTUK MENGEMBANGKAN KOMPETENSI PENGECORAN DI SMK PROGRAM STUDI KEAHLIAN TEKNIK MESIN - Somawidagdo, Arianto Leman; Tiwan, -; Mujiyono, - (Universitas Negeri Yogyakarta, 2014)
The program is aimed at developing casting competence at SMKMuhammadiyah Prambanan Yogyakarta by developing gas fueled aluminiumcrucible furnace. Research and development method was used todevelop aluminium crucible furnace. Training on crucible furnace operationand aluminium casting for SMK Muhammadiyah teachers was done usingdemonstration and lecture method. The program result is (í˜600x500)mmcrucible furnace with capacity of 15 kg melted aluminium. The furnace need2,7 kg of LPG and 55 minutes to melt 8,6 kg aluminium. SMK MuhammadiyahPrambanan teachers are able to operate the furnace, to make a sandmold and to do a daily and special maintenance.Keywords: Crucibel furnace, Aluminium, Casting competence, SMK, andMechanical Engineering